The Influence of Facilities, Academic Staff Services and Lecturer Services on Student Satisfaction at the Faculty of Economics and Business, University of Yogyakarta State - Kusnadi Kusnadi; Aula Ahmad Hafidh Saiful Fikri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Student satisfaction is an important issue because it will further influence the overall assessment of the university. Skills and skills factors, facilities/facilities factors, lecturer discipline factors, academic and non-academic service factors, learning activity factors, lecture suitability factors, campus access factors, campus security factors and finally the lecturer counseling factor, are factors that influence satisfaction. student. The aim of this research is to determine the influence of facilities, personnel services, academics and lecturer services on student satisfaction at the Faculty of Economics and Business, Yogyakarta State University. This research is a quantitative study with a cross sectional approach. The population in this study were all students at the economics and business faculty at Yogyakarta State University with a sample of 120 people. The sampling technique in this research was obtained using a simple side random method. The research results show that there is no influence of facilities on student satisfaction with a significant value of 0,112. There is an influence of academic services on student satisfaction with a significant value of 0,008. There is an influence of lecturer service on student satisfaction with a significant value of 0,000. There is an influence of facilities, academic services and lecturer services on student satisfaction at the economics and business faculty of Yogyakarta State University with a significant value of 0,000.